Phytochemical Screening and Acute Toxicity Study of Cucumis metuliferus E. Mey. Ex. Naudin Fruit Extract in Cockerels - Joy Gararawa Usman; OA Sodipo; UK Sandabe (International Journal of Phytomedicine, 2014)
The ripe fruits of Cucumis metuliferus were collected at Vom, Jos South Local Government Area of Plateau State, cleaned, sliced, air-dried, pulverised and cold extracted with solvents of different polarities (n-hexane, chloroform, methanol and distilled water). The ground powder and the extracts obtained were phytochemically screened for their chemical composition. These revealed the presence of saponins, alkaloids, carbohydrates, flavonoids, tannins, cardiac glycosides, steroids and terpenoids. The median lethal dose (LD50) of the methanol extract was determined in chicken by oral (p.o) and intra-peritoneal (i.p) routes. An LD50 above 5000 mg/kg body weight was established for both routes, indicating that probably the fruit of C. metuliferus is not toxic.